RELIGIOUS-BASED HABITUATION AND THE CULTIVATION OF INTERRELIGIOUS HARMONY IN SCHOOL CULTURE - Ilmi Nur Hidayah; Imas Kurniawaty; Muhamad Parhan (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2025)
This study examines how religious-based habituation strengthens school culture and fosters interreligious harmony in a religiously diverse public elementary school. Although previous research has explored school culture and religious habituation separately, empirical evidence is limited on how daily religious routines can function as inclusive social mechanisms that promote interfaith tolerance. This study addresses this gap by analyzing the implementation and impact of religious habituation at SDN 116 Cicaheum. A mixed-methods sequential exploratory design was employed. Qualitative data were collected through observations, interviews with the principal, teachers, and students, and documentation. Quantitative data were obtained from questionnaires administered to 30 sixth-grade students and analyzed using validity and reliability testing, followed by simple linear regression. The findings show that religious habituation is implemented through daily routines such as the 5S movement, collective prayers, and Qur’anic recitation, as well as weekly activities including Dhuha prayer, short sermons, and mini religious projects. These practices are designed inclusively, allowing students of different faiths to participate through alternative moral and social activities. Quantitative analysis indicates a positive and significant effect of religious habituation on school culture, with a regression coefficient of 1.645 and a significance value below 0.001. The study demonstrates that inclusive religious habituation not only strengthens students’ spiritual character but also creates structured opportunities for interfaith interaction aligned with Intergroup Contact Theory. It concludes that adaptive habituation programs can be effective strategies for cultivating tolerance and a a harmonious school culture in multicultural educational settings. AbstrakPenelitian ini mengkaji bagaimana habituasi berbasis religius berkontribusi pada penguatan budaya sekolah dan penumbuhan harmoni antarumat beragama di sebuah sekolah dasar negeri yang memiliki keragaman agama. Meskipun penelitian sebelumnya telah membahas budaya sekolah dan habituasi religius secara terpisah, masih terbatas bukti empiris yang menjelaskan bagaimana rutinitas keagamaan harian dapat berfungsi sebagai mekanisme sosial inklusif yang mendorong toleransi antaragama. Penelitian ini mengisi kesenjangan tersebut dengan menganalisis implementasi dan dampak habituasi religius di SDN 116 Cicaheum. Penelitian ini menggunakan desain mixed methods sequential exploratory. Data kualitatif dikumpulkan melalui observasi, wawancara dengan kepala sekolah, guru, dan siswa, serta dokumentasi. Data kuantitatif diperoleh melalui kuesioner yang diberikan kepada 30 siswa kelas VI dan dianalisis melalui uji validitas, reliabilitas, serta regresi linier sederhana. Temuan menunjukkan bahwa habituasi religius dilaksanakan melalui kegiatan harian seperti gerakan 5S, doa bersama, dan pembacaan Al‑Qur’an, serta kegiatan mingguan seperti salat Dhuha, kultum, dan proyek religius mini. Praktik-praktik ini dirancang secara inklusif sehingga siswa dari berbagai agama dapat berpartisipasi melalui aktivitas moral dan sosial alternatif. Analisis kuantitatif menunjukkan adanya pengaruh positif dan signifikan habituasi religius terhadap budaya sekolah, dengan koefisien regresi sebesar 1,645 dan nilai signifikansi di bawah 0,001. Penelitian ini menunjukkan bahwa habituasi religius yang inklusif tidak hanya memperkuat karakter spiritual siswa tetapi juga menciptakan peluang interaksi antaragama yang terstruktur sesuai dengan Intergroup Contact Theory. Penelitian ini menyimpulkan bahwa program habituasi yang adaptif dapat menjadi strategi efektif untuk menumbuhkan toleransi dan budaya sekolah yang harmonis dalam konteks pendidikan multikultural.